The Influence of Adding LDPE-g-AO Compatibilizer on the Properties of Polyethylene/Polyamide Blends - Barita Aritonang; Ahmad Hafizullah Ritonga; Karnirius Harefa; Herlina; Dicky Yuswardi Wiratma (Jurnal Indah Sains dan Klinis, 2024)
Background: The primary reason for the immiscibility of polyethylene (PE) and polyamide (PA) lies in their differing polarities and surface tension energies. Objective: This study aims to investigate the impact of LDPE-g-AO compatibilizer on PE/PA blends. Method: The method employed involves blending using an internal mixer. Results: SEM analysis reveals that the morphology of PE/PA blends without LDPE-g-AO compatibilizer is non-homogeneous and incompatible. However, the addition of 2% LDPE-g-AO compatibilizer results in improved compatibility of the PE/PA blend, characterized by homogeneous and compatible surface adhesion properties, with no visible voids. Conclusion: In conclusion, this research underscores the effectiveness of LDPE-g-AO compatibilizer in bridging two previously immiscible polymers, PE and PA, thereby enhancing their overall compatibility